Older Mothers' Employment and Marriage Stability When the Nest Is Empty - Hippolyte D'Albis; Karina Doorley; Elena G. F. Stancanelli (Institute of Labor Economics (IZA), 2022)
A significant literature in the social sciences addresses the impact of child-bearing and rearing on marital stability and on mothers' labour market outcomes. Much less is known about older mothers' employment and marriage patterns when the adult children leave the parental nest. This study aims to shed light on these issues using longitudinal labour force data for France. Exploiting retirement laws for identification purposes, and taking a regression discontinuity approach, we find that older women's retirement probability is positively associated with an empty nest. We also conclude that an empty nest is negatively associated with older mothers' marriage probability. There is scope for better targeting of both family and retirement policies for older mothers during those critical years when adult children leave the parental nest.
Keywords: J12; J14; J22; 330; retirement; ageing; divorce